Assessment of health-related quality of life among Arabic speaking immigrants in Sultanbeyli - Istanbul - Mohammed, Asmaa Z. F. (My University, 2020)
Objective: Migration is a global phenomenon and creates a sudden/ rapid environmental change, affects society and individuals. It was objected to evaluate the health-related quality of life (HRQOL) among Arabic speaking immigrants living in Sultanbeyli–Istanbul.Material and methods: Data for this descriptive study collected from Arabic-speaking immigrants registered in the Association for Refugees in Sultanbeyli/ Istanbul through face-to-face interviewer by using a questionnaire in Arabic, including items about socio-demographic characteristics, HRQOL(SF-36), and reproductive health of ever-married-women (EMW). Data analyzed by using SPSS11.0.Results: In this study, 379 participants were interviewed (age:19-79, median.33,0 years). More than half were females (57,5%), most of the respondents (85,5%) were ever married, and 29,6% of ever-married-women had more than four children. One-third of participants (36,7%) completed primary schools. The HRQOL scores among females were lower than those of males in the physical-function subscale (80,0 vs. 85,0, p:0.033). The youngest age group had higher physical-function, body-pain, general-health, and role-limitation-physical scores (p:0.0001, p:0.0001, p:0.0001, p:0.047). There were significant differences in HRQOL domains due to educational-attainment, employment-status, and known-language. Physical-function, body-pain, role-limitation-physical, and role-limitation-emotional scales were significantly affected by the number of living children for EMW.Conclusion: Our findings show that Arabic-speaking-immigrants residing in Sultanbeyli/ Istanbul have HRQOL scales relatively moderate. The HRQOL is significantly influenced by age, educational attainment, employment status, and known language. It is recommended to implement the Turkish language and vocational courses for immigrants. Family planning services should be taken place in Refugee Associations.

Amaç: Göç küresel bir olgudur ve ani/ hızlı bir çevresel değişim yaratır, toplumu ve bireyleri etkiler. Bu çalışmada İstanbul–Sultanbeyli'de yaşayan Arapça konuşan göçmenlerin arasında Sağlıkla İlgili Yaşam Kalitelrinin (SYK) değerlendirilmesi amaçlanmaktadır.Gereç ve yöntem: Bu tanımlayıcı çalışma için veriler, İstanbul/ Sultanbeyli’deki Mülteciler Derneği'ne kayıtlı Arapça konuşan göçmenlerden, sosyo-demografik özellikler, SYK (SF-36) ve evli kadınların (EK) üreme sağlığı ile ilgili konularını içeren Arapça bir anket kullanılarak yüz-yüze görüşme yöntemiyle toplanmıştır. Veriler SPSS11.0 kullanılarak analiz edilmiştir.Bulgular: Bu çalışmada 379 katılımcı ile görüşülmüştür (Yaş aralığı:19-79, Ortanca yaş: 33 yıl). Katılımcıların yarıdan fazlası kadındır (%57,5), katılımcıların çoğunluğu (85,5%) evliydi ve kadınların %29,6'sı dörtten fazla çocuğa sahipti. Katılımcıların üçte-biri (36,7%) ilkokul mezunuydu. Kadınların SYK puanı, fiziksel-fonksiyon alt ölçeğinde erkeklerden daha düşüktü (80,0 vs. 85,0, p:0.033). En genç grup daha yüksek fiziksel-fonksiyon, vücut-ağrısı, genel-sağlık ve rol-sınırlaması-fiziksel puanlarına sahipti (p:0.0001, p:0.0001, p:0.0001, p:0.047). Eğitim düzeyilerine, istihdam durumlarına ve bildikleri dillere göre SYK´lerinde önemli farklılıklar vardı. Evli kadınların yaşayan çocuk sayıları fiziksel-fonksiyon, vücut-ağrısı, rol-sınırlaması-duygusal ölçeklerini önemli ölçüde etkilemekteydi.Sonuç: Bulgularımız, İstanbul-Sultanbeyli'de ikamet eden Arapça konuşan göçmenlerin SYK ölçeklerinin nispeten ılımlı olduğunu göstermektedir. Katılımcıların SYK´in, yaş, eğitim seviyesi, istihdam durumu ve bildikleri dilden önemli ölçüde etkilendiği saptanmıştır. Göçmenler için Türkçe ve mesleki kursların açılmasını öneriyoruz. Mülteci Derneklerinde aile planlaması danışmanlık ve hizmetlerinin sunumuna çok gereksinim vardır.
Keywords: Göçmenler; Halk sağlığı; Immigrants; Kısa Form-36; life quality; Migration; mülteci; Public health; Quality of life; refugee; Short Form-36 Göç; Turkey; Türkiye; Yaşam kalitesi